1994
DOI: 10.1007/bf00169367
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition by ethanol of excitatory amino acid receptors and nicotinic acetylcholine receptors at rat locus coeruleus neurons

Abstract: The frequency of spontaneous action potentials of locus coeruleus (LC) neurons was recorded extracellularly in pontine slices of the rat brain. Ethanol (1-100 mM) elevated the firing rate in most neurons; this effect was concentration-dependent. (S)-alpha-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA; 0.03-1 microM), kainate (0.1-3 microM), N-methyl-D-aspartate (NMDA; 1-30 microM), substance P (0.01-1 microM), nicotine (0.1-10 microM) and alpha,beta-methylene ATP (alpha,beta-meATP; 0.3-30 microM), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 26 publications
2
15
1
Order By: Relevance
“…These data are in partial contradiction with previous extracellular experiments, where ethanol (100 mM) increased the firing rate (Fröhlich et al 1994). Although the reason for this discrepancy is unknown, it has to be considered that extracellular, in contrast to intracellular microelectrodes may activate previously silent neurons by mechanical irritation.…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…These data are in partial contradiction with previous extracellular experiments, where ethanol (100 mM) increased the firing rate (Fröhlich et al 1994). Although the reason for this discrepancy is unknown, it has to be considered that extracellular, in contrast to intracellular microelectrodes may activate previously silent neurons by mechanical irritation.…”
Section: Discussioncontrasting
confidence: 92%
“…Previous extracellular experiments documented a concentration-dependent inhibition by ethanol (10, 100 mM) of the NMDA-induced increase in the firing rate of LC neurons (Fröhlich et al 1994). The two compounds were suggested to interact in a truly antagonistic manner, since their effect on co-application was less than the sum of their individual effects.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Some have argued that EtOH is simply a co-agonist and requires NIC to elicit a cholinergic response [85]. However, EtOH is not only a co-agonist in the presence of a ligand binding to cholinergic receptors, but also operates directly on some types of nAChRs in vitro [83,86] and in vivo [87][88][89]. The sensitivity and effects elicited by EtOH binding to nAChRs are dependent upon subunit composition [90].…”
Section: Nicotinic Acetylcholine Receptors and Ethanolmentioning
confidence: 99%
“…Historically, it was thought the most likely mechanism for this modulation was the inhibitory action of ethanol at the NMDA subtype of the glutamate receptor. Preclinical studies have shown acute exposure to ethanol dosedependently attenuates NMDA-evoked currents in hippocampal (Lovinger et al, 1990) and locus coeruleus neurons (Frölich et al, 1994), blocks extracellular striatal increases in glutamate caused by focal application of NMDA (Carboni et al, 1993), and protects against NMDA-induced convulsions (Kulkarni et al, 1990) in rats. Furthermore, the NMDA antagonists ketamine, MK-801, and phencyclidine substitute for ethanol in animal drug discrimination studies (Grant et al, 1991;Colombo and Grant, 1992;Schecter et al, 1993), and ketamine has ethanol-like effects in healthy subjects (Krystal et al, 1994) and recently detoxified alcoholics (Krystal et al, 1998).…”
Section: Introductionmentioning
confidence: 99%